Komunikasi Orangtua Terhadap Perilaku Anak di Jalan Damar 14 Perumnas Simalingkar - Emelia Agustina Sinaga; Suheri Harahap; Muhammad Faishal (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The purpose of this study is to find out how the communication that occurs between parents and their children at Perumnas Simalingkar and to determine the behavior of children at Perumnas Simalingkar. This study uses qualitative research methods with the aim of understanding the phenomenon in the research subject by describing it in the form of words or natural language. The theory used in this study is the theory of effective communication. The subjects in this study were children at Perumnas Simalingkar Jalan Damar 14. From the results of this study it can be concluded that positive parental communication will result in positive child behavior and negative parental communication will produce negative child behavior.